Evaluación del Daño y Restauración de los Árboles Después de un Huracán - Edward F. Gilman; Mary L. Duryea; Eliana Kampf; Traci Jo Partin; Astrid Delgado; Carol J. Lehtola (EDIS)
ENH-1037, a 16-page full-color fact sheet by Edward F. Gilman, Mary L. Duryea, Eliana Kampf, Traci Jo Partin, Astrid Delgado, and Carol Lehtola is the Spanish language version of ENH-1036, "Assessing Damage and Restoring Trees after a Hurricane", funded by the Florida Division of Forestry and the USDA Forest Service, Southern Region as part of the Urban Forest Hurricane Recovery Program. Includes sections with guidelines for chainsaw safety, how to hire tree care professionals, how to tell which damaged trees can recover and which should be removed, how to restore trees to health after a hurricane by pruning -- both immediately after the storm and after few years' growth, specialized information for dealing with palm and pine trees, how to prevent damage by using effective design and management practices, and lists of decay resistant and wind resistant tree species for Florida. Published by the UF Department of Environmental Horticulture, July 2006.